Serum adenosine deaminase levels and other laboratory parameters in the diagnosis of extrapulmonary tuberculosis: a clinicopathological study - Mugulkod, Prabhavati; S., Sateesh Chavan (International Journal of Research in Medical Sciences, 2017)
Background: Diagnosis of extra pulmonary tuberculosis (EPTB) is difficult due to its nonspecific signs and symptoms and paucibacillary nature. Early diagnosis and institution of appropriate therapy is essential to reduce the morbidity. The aim of the study was to study correlation between clinical findings, cytological/histological findings of EPTB with other laboratory parameters such as erythrocyte sedimentation rate (ESR), acid fast bacilli (AFB) status on Ziehl Neelson (ZN) stained sections /smears and serum adenosine de aminase (ADA) levels. Methods: All histologically and cytologically diagnosed cases of EPTB were included in the study and were examined for AFB on ZN stained smears and correlated with clinical findings and laboratory parameters such as ESR and serum ADA levels. Results: A total number of 230 cases of extrapulmonary tuberculosis were studied. Most common site of EPTB was lymph nodes. The most common age group affected was 3rd and 4th decade. Over half of the patients were females with male to female ratio 1:1.03. Majority had elevated ESR and caseating granuloma and only minority showed AFB positivity. Serum adenosine de aminase levels were raised in 83.3% (45 out of 54 cases). Majority of cases of EPTB with raised serum ADA levels had elevated ESR but negative for acid fast bacilli. Conclusions: Both histopathology (including cytology smears) as well as Ziehl Neelsen smears for acid fast bacilli are an “independent” diagnostic parameter and still be considered as “gold standard” while serum ADA levels are most valuable surrogate parameter.